The Realization of Speech Act of Requesting: An Analysis of Movie Freedom Writers - Cakrawati, Laxmi Mustika; Wijayanti, Lely Tri (Foremost Journal, 2023)
Language learners are required to be able to use the language they learn in an appropriate context. By mastering pragmatic competence, it is expected that language learners comprehend how to use the language and how to interpret the meaning of the language in a particular setting. This study attempts to explore the realization of the speech act of requesting in a movie entitled Freedom Writers. To be specific, this study aims to figure out strategy types and modification devices of requesting used by the characters in the movie as well as its pedagogical implication for English language learning. By employing a case study design, this study analyzed the script of the movie and classified the request under the framework of A Cross-Cultural Study of Speech Act Realization Patterns (CCSARP). The findings reveal that mood derivable and scope stating are the most frequent strategies used and regarding the modification devices, the characters tend to use internal modifiers such as syntactic downgraders and upgraders. The results of the study suggest teacher to provide some authentic materials to introduce students to the real use of language. Further studies about speech acts focusing on the pedagogical implication are encouraged to be conducted. Keywords: speech act of requesting, CCSARP, pragmatic competence